2017
DOI: 10.1111/cts.12497
|View full text |Cite
|
Sign up to set email alerts
|

LY3127760, a Selective Prostaglandin E4 (EP4) Receptor Antagonist, and Celecoxib: A Comparison of Pharmacological Profiles

Abstract: Safety, tolerability, and pharmacology profiles of LY3127760, an EP4 antagonist, were explored in healthy subjects in a subject/investigator‐blind, parallel‐group, multiple‐ascending dose study. Cohorts consisted of 13 patients randomized to LY3127760, celecoxib (400 mg), or placebo (9:2:2 ratio) for 28 days. LY3127760 was well tolerated; the most commonly observed adverse events were gastrointestinal, similar to celecoxib. LY3127760 increased release of ex vivo tumor necrosis factor alpha after lipopolysaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 11 publications
1
26
1
Order By: Relevance
“…EP4 could represent a promising target to inhibit Th17 cell development in AS. Specific EP4 antagonists have been developed and their efficiency to inhibit Th17 cells has been tested in vitro [62][63][64]. Selective inhibition of EP4 could represent a promising strategy to reduce Th17 cell frequencies and disease activity in AS.…”
Section: Discussionmentioning
confidence: 99%
“…EP4 could represent a promising target to inhibit Th17 cell development in AS. Specific EP4 antagonists have been developed and their efficiency to inhibit Th17 cells has been tested in vitro [62][63][64]. Selective inhibition of EP4 could represent a promising strategy to reduce Th17 cell frequencies and disease activity in AS.…”
Section: Discussionmentioning
confidence: 99%
“…Application of the asymmetric sp 2 -sp 3 Suzuki-Miyaura methodology [22] enabled the synthesis of clinical candidates preclamol (15, a dopamine D2 receptor partial agonist studied for the treatment of schizophrenia), niraparib (16, MK−4827, a 2017 approved poly-(ADP ribose) polymerase (PARP) inhibitor indicated for ovarian cancer), and natural product isoanabasine (17), which are all presented in Figure 3 with their corresponding Fsp 3 values calculated using SwissADME [23] online tool. An example of the trend to increase Fsp 3 during the Lead Optimization phase, leveraging crosscoupling reactions in drug design, comes from the evolution of the SAR approach for novel Eprostanoid receptor 4 (EP4) antagonists ( Figure 4) [24,25] that eventually led to the discovery of LY3127760 [26]. An initial lead (naphthalene derivative, 18) [27] was identified through an early medicinal chemistry effort, possessing modest human whole blood activity (hWB, IC50 = 243 nM) and low Fsp 3 .…”
Section: C-c Reaction: Suzuki-miyaura Reactionmentioning
confidence: 99%
“…The selective EP4 antagonist grapiprant has been approved for the treatment of osteoarthritis pain in dogs (Rausch-Derra et al 2016). Recently, a clinical study demonstrated that the selective EP4 antagonist LY3127760 at daily doses of 60 mg to 600 mg was safe and tolerable in healthy subjects during oral dosing for 28 days (Jin et al 2018). It has been reported that LY3127760 had therapeutic effects on animal models of monoiodoacetate-induced osteoarthritis, adjuvant arthritis, and migraine headache (Blanco et al 2016).…”
Section: Discussionmentioning
confidence: 99%